Te Tipu a te Kūmara Factors that Influence Rangatahi Māori from Dargaville, Northland to Pursue University Education - Poutama, Josephine (Auckland University of Technology, 2016)
Dargaville, a small rural town situated in the North Island of New Zealand, has a high proportion of Māori who do not choose to go on to university education or tend to leave school before they attain University Entrance (Statistics New Zealand, 2006). This study examines which factors influence rangatahi (youth) Māori from Dargaville, Northland to pursue university education. By analysing selected influencing factors, this thesis provides an understanding into ways in which whānau, communities, and schools can work together to benefit the future rangatahi Māori of Dargaville. This thesis reflects a Māori world-view, specifically how Māori view the world as holistic and cyclic. The method that was used in this thesis is grounded in Kaupapa Māori theory. Kaupapa Māori has guided this research through the adoption of key Māori principles. Qualitative interviews were conducted in this research, where the participants had the option of meeting face to face with the researcher or interviewing via Skype. Indigenous research ethics were also practiced in the research as all participants are Māori. Abiding by Māori protocols was very important in making sure that the Treaty of Waitangi principles were upheld. The identified model of success designed and created by the researcher will provide the community and schools of Dargaville with an outline of requirements for students looking to pursue university education. The model uses the kūmara (sweet potato) and compares the growth of a kūmara to the growth and journey of an individual from Dargaville. From the sprouting kūmara, representing the student, to the complete kūmara, where the student has successfully completed high school with the correct grades to be able to enter university. One of the conclusions reached in this study is that whānau play a pivotal role in providing students with the option to attend university. The relationship maintained between student, parents, and wider whānau members is important to the success of a student who is planning on pursuing university study.
Keywords: Youth; University education; Rangatahi; Youth development; Dargaville; Northland; Higher education; Tertiary education; Barriers; Māori; Kūmara